A STUDY ON THE RELEVANCE OF MATERIALS IN ENGLISH TEXTBOOK “BRIGHT” FOR SEVENTH GRADERS OF JUNIOR HIGH SCHOOL PUBLISHED BY ERLANGGA TO 2013 CURRICULUM (RETAIN, 2014)
A STUDY ON THE RELEVANCE OF MATERIALS IN ENGLISH TEXTBOOK “BRIGHT” FOR SEVENTH GRADERS OF JUNIOR HIGH SCHOOL PUBLISHED BY ERLANGGA TO 2013 CURRICULUM Halimatul Kamila English Study Program, FBS, Surabaya State University halimatulkamila@gmail.com Ririn Pusparini, S.Pd., M.Pd. Lecturer of English Study Program, FBS, Surabaya State University rrn.puspa@gmail.com Abstract The Indonesia government has developed English standard competence which is stated in curriculum as the standard of teaching and learning English process. According to the curriculum, material is one of the important factors for determining the success of the teaching and learning process. The material which is usually used is in the form of textbook. Textbook must be in line with the components stated in curriculum. Although there are many textbooks that are claimed as a suitable material for 2013 Curriculum, it is not a guarantee that the textbook is relevant to the standard competences of the curriculum. An analysis to a textbook is needed, moreover after the new curriculum was launched. Based on the background of the case above, this study is conducted: 1) to analyze the relevance of the materials with the cognitive aspects which are contained in the 2013 English Standard Competence, 2) to analyze the relevance of the materials with the psychomotor aspects which are contained in the 2013 English Standard Competence. This study was designed in descriptive qualitative research because the object of the study was a documented book. Moreover, as the data was in the form of words and documents, so the data were analysed qualitatively. The instrument used to collect the data is observation in the form of checklists. After being analyzed, it is found that some of the materials are not relevant with the cognitive and psychomotor aspects which are contained in the 2013 English Standard Competence. However, there are more materials which relevant with with the 2013 English Standard Competence than the materials which not. Thus, it can be concluded that the materials in this textbook are quite relevant with 2013 curriculum, especially with the cognitive and the psychomotor aspects. Therefore, this textbook is appropriate with the 2013 curriculum and suitable to be used in order to help the teaching and learning process in the classroom. Keywords: analysis, relevance, materials, textbook, the 2013 Curriculum. Abstrak Pemerintah Indonesia telah mengembangkan standar kompetensi Bahasa Inggris yang disampaikan dalam kurikulum sebagai acuan dalam proses belajar mengajar. Berdasarkan kurikulum, bahan pelajaran adalah saah satu faktor penting untuk menentukan suksesnya proses belajar mengajar. Bahan pelajaran yang umum digunakan adalah buku teks. Buku teks yang digunakan harus sesuai dengan komponen-komponen yang disampaikan dalam kurikulum. Meski banyak buku teks yang telah dinyatakan sebagai bahan pelajaran yang sesuai dengan Kurikulum 2013, tidak menjadi jaminan bahwa buku teks tersebut relevan dengan standar kompetensi dalam kurikulum. Analisis terhadap buku teks sangat dibutuhkan, terutama setelah diluncurkannya kurikulum baru. Berdasarkan latar belakang tersebut, penelitian ini dilaksanakan: 1) untuk menganalisis kecocokan antara bahan pelajaran dalam buku teks “Bright” dengan aspek kognitif yang terdapat dalam Standar Kompetensi Bahasa Inggris 2013, 2) untuk menganalisis kecocokan antara bahan pelajaran dalam buku teks “Bright” dengan aspek psikomotor yang terdapat dalam Standar Kompetensi Bahasa Inggris 2013. Metode penelitian yang digunakan adalah deskriptif kualitatif karena objek yang menjadi bahan penelitian adalah buku. Selain itu, data penelitian dianalisis secara kualitatif karena data yang digunakan dalam penelitian ini berbentuk dokumen. Instrumen yang digunakan dalam penelitian ini adalah observasi dalam bentuk checklists. Setelah dianalisis, ditemukan bahwa beberapa bahan pelajaran di dalam buku teks tidak relevan dengan aspek kognitif dan psikomotor yang terdapat dalam Standar Kompetensi Bahasa Inggris 2013. Akan tetapi, lebih banyak bahan pelajaran yang sesuai dengan Standar Kompetensi Bahasa Inggris 2013 daripada yang tidak sesuai. Jadi, dapat disimpulkan bahwa bahan pelajaran dalam buku teks ini cukup relevan dengan kurikulum 2013, terutama dengan aspek kognitif dan psikomotor. Oleh karena itu, buku teks ini sesuai dengan kurikulum 2013 dan layak digunakan untuk membantu proses belajar mengajar di dalam kelas. Kata Kunci: analisis, relevansi, bahan pelajaran, buku teks, kurikulum 2013. INTRODUCTION English plays a very important role as a means of communication. It is because English is an international language that can be used for international communication. Knowing that English as an international language is necessary in facing globalization, English as a foreign language is being taught and learnt in many countries, included in Indonesia. As the main foreign language in this country, English has become a compulsory subject in Junior High School until Senior High School. Indonesia government has implemented English into the academic curriculum. The government has developed English standard competence which is stated in curriculum as the standard of teaching and learning English process. Curriculum is made based on the Indonesian learners’ need and is developed to achieve the certain aim of education. Because of the development of the human needs, especially in education field, the Indonesian government always trying to make a better standard for teaching and learning process. As stated by Nunan (2003:5) that “For many years, the goal of language pedagogy was to find the right method.” That is why, Indonesian government especially the National education department develops a new curriculum as the new standard for teaching and learning process. Recently, by Peraturan Pemerintah 32/2013, the educational system of Indonesia has launched Kurikulum 2013. Kurikulum 2013 is a school based curriculum, it is an operational curriculum which is constructed, developed, and implemented by each education unit (school). The purpose of the 2013 Curriculum is to draw up the next generations of Indonesia to be a religious, productive, creative, and innovative citizen who could contribute for the social life in the Indonesia and social life in all over the world (Permendikbud Nomor 68 Tahun 2013). The English standard competences in 2013 Curriculum are conducted in particular purposes, they are: the purpose of affective aspects, cognitive aspects, and psychomotor aspects (Amri, 2013:39). Affective is the aspect which related to emotion, feeling and attitude. Cognitive is the aspect which related to knowledge. While psychomotor aspect is related to motor skill. According to the curriculum, material is also important in creating a good teaching and learning process. Material is one of the factors for determining the success of the teaching and learning process. The material which is usually used is in the form of textbook. In fact, mostly Indonesian teachers use textbook in delivering the material. Textbook is one of the learning materials that can be used by teacher and students in order to help the teaching and learning process in the classroom (Tomlinson, 2003). Textbook is an important component in the process of teaching and learning. It is because textbook can be a main resource for the teachers in guiding them in the teaching and learning activity. Textbook must be in line with the components stated in curriculum. However, selecting a textbook is not an easy job for the teachers. They should be careful in choosing an appropriate textbook, it is a textbook which supports the implementation of the curriculum. As Byrd (2001) says, textbook evaluation should be viewed in terms of the relevance between the textbook and the curriculum. Although there are many textbooks that are claimed as a suitable material for 2013 Curriculum, it is not a guarantee that the textbook is relevant to the standard competences of the curriculum. Based on the explanation above, textbook analysis is one of the efforts that can be done in determining whether a textbook is appropriate with the curriculum or not. An analysis to a textbook is still needed, moreover after the new curriculum was launched. Thus, this study was conducted to analyse the materials in English textbook for seventh graders entitled “Bright” published by Erlangga. In this study, the researcher wanted to find out the relevance of the materials in the textbook to the 2013 English Standard Competence. Based on the elaboration above, the objectives of this study are formulated as follow: 1. To analyse the relevance of the materials with the cognitive aspects which are contained in the 2013 English Standard Competence. 2. To analyse the relevance of the materials with the psychomotor aspects which are contained in the 2013 English Standard Competence. Curriculum Teaching and learning process in a school is performed based on the curriculum. The curriculum is designed by the government, so that everyone could get same experience in education (Ali, 2009:1). The Indonesian government defines curriculum as a set of plan and systematization of aims, contents, materials as the guidance in the process of teaching and learning to achieve the certain goal (Permendikbud Nomor 68 Tahun 2013). According to Ali (2009:15), curriculum has a strong influence in the process of teaching and learning. The curriculum as the plan for learning contains of some aspects and purposes which are related to the teaching and learning activity. In the curriculum, also contain the objectives of the study which should be achieved by the learners. Therefore, the good teaching and learning process should be performed based on the curriculum. Oliver (1977:329) states that as the product of the thinking and action of human beings, curriculum should be improved. As the ideas of people change, as people’s actions change, so does curriculum. Curriculum is developed based on the objectives and the learners’ need. Therefore, the Indonesian government can change and improve the curriculum, if the previous curriculum is not suitable with the objectives and Indonesian learners’ need. Recently, by Peraturan Pemerintah 32/2013, the educational system of Indonesia has launched Kurikulum 2013. The 2013 Curriculum The 2013 Curriculum is a school based curriculum, it is an operational curriculum which is constructed, developed, and implemented by each education unit (school) since 2013. The 2013 Curriculum is legalized by Ministry of National Education in 2013. The 2013 Curriculum contains of the plan for teaching and learning process, the rules of objectives and materials, and the method used in the process of teaching and learning (Permendikbud Nomor 68 Tahun 2013). The 2013 Curriculum is designed in three aspects, they are: affective, cognitive, and psychomotor. Affective aspects encourage students to; accept, perform, appreciate, and inspire. Cognitive aspects encourage students to; comprehend, apply, analyse, and evaluate. While psychomotor aspects encourage students to; observe, ask, try, find reasons, present, and compose (Permendikbud Nomor 65 Tahun 2013). The learning stages that are emphasized in the 2013 Curriculum are: 1) observing; the students collect the information, 2) questioning; the students are stimulated to question how the phenomena happen, 3) experimenting; the students try to apply the knowledge through some practice given by the teacher, 4) associating; the students try to relate the phenomena to the previous knowledge, and 5) communicating; the students tell others about their finding. The 2013 English Standard Competence contains some English basic competences which cover all of the English materials. According to the 2013 Curriculum, English Standard Competence contains two kinds of competences, they are: core competences and basic competences. Core competence is divided into four objectives. The first and second objectives emphasize on affective domain. The third objectives emphasize on cognitive domain, and the forth objectives emphasize on psychomotor domain. Each of the core competence is divided into basic competences which are used as a guideline in developing learning materials (Permendikbud Nomor 68 Tahun 2013). The Three Domains of Learning According to Krathwohl, Bloom and Masia (1973), objectives of study could be placed in one of three major domains, they are: cognitive, affective, and psychomotor. Bloom et al. (1956) in Ali (2009:78-81) explains about those three domains as follows: Cognitive Cognitive domain related to the learner’s thinking. This objective emphasizes remembering or reproducing something which has been learned. Cognitive objectives vary from simple recall of material learned to highly original and creative ways of combining and synthesizing new ideas and materials. Bloom et al. (1956) states the learning level of cognitive domain, they are: knowledge, comprehension, application, analysis, synthesis, and evaluation. Anderson (2001) revises the cognitive domain in the learning taxonomy and made some changes. The most prominent changes are: 1) the names in the six categories from noun to verb forms, and 2) slightly rearranging them. The revised cognitive domain are: remembering, understanding, applying, analysing, evaluating, and creating. Affective Affective domain related to the learner’s attitude. This objective emphasizes a feeling, an emotion, or a degree of acceptance or rejection. Affective objectives vary from simple attention to selected phenomena to complex. Krathwohl et al. (1973) mentions the affective domain as: receive, respond, value, organise or conceptualize values, and internalize or characterise values. Psychomotor Psychomotor domain related to the learner’s skill. This objective emphasizes some muscular or motor skill, some manipulation of material and objects, or some acts which requires a neuromuscular co-ordination. Dave (1975) mentions the psychomotor domain as: imitation, manipulation, precision, articulation, and naturalization. Textbook Textbook is an important component in the process of teaching and learning. It is because textbook can be a main resource for the teachers in guiding them in the teaching and learning activity. However, selecting a textbook is not an easy job for the teachers. They should be careful in choosing an appropriate textbook. Byrd (2001) explains the criteria that should be used in evaluating and choosing a good textbook. They are: 1. The fit between the material and the curriculum Curriculum is a guidance of teaching and learning process, including the purposes of the program and the teaching procedures. Therefore, the fit between the material and the curriculum would help the students to achieve the goal of the program. 2. The fit between the material and the students Textbook is used by the students. Therefore, the materials should be fit with the students’ needs, so that they can learn the materials effectively. 3. The fit between the material and the teacher Textbook is used by the teacher. Therefore, the materials in the textbook should help the teacher in organizing the process of teaching and learning effectively. Textbook is often used in schools, and schools follow the curriculum designed by the government to guide the teachers in developing the objectives of teaching and learning activities. Therefore, Tarigan and Tarigan (1990:22) add that a good textbook should be relevant with the curriculum. Textbook is very important in supporting teaching and learning process. Therefore, a textbook must be in line with the components stated in the curriculum. The materials in the textbook should be designed based on the competences stated in curriculum. A textbook should support the curriculum to achieve the instructional objectives. A textbook should support the three domains that become the objectives of the 2013 English Standard Competence, they are: cognitive, affective, and psychomotor. RESEARCH METHOD This research is concerned in analysing the relevance of materials in the English textbook entitled “Bright” published by Erlangga to the 2013 Curriculum. Whether the textbook presents the purposes of the 2013 English standard competence or not. Since this study dealt with analysis of the content of textbook especially the materials, the data were analysed qualitatively, without any statistical calculation. As Ary et al. (2010:424) states that qualitative researcher deals with data that are in the form of words or pictures rather than numbers and statistics. Moreover, as the data was in the form of words and documents, so the data were analysed qualitatively. The data of this study is an English textbook entitled “Bright” for seventh graders of Junior High School published by Erlangga. The data are in the form of documented materials existing in the textbook. The materials are divided into some activities. The data were analysed in order to answer the research problems stated in Chapter I. There are several instruments which were needed to collect the data. According to Ary et al. (2010:421), the primary instrument used for collecting the data in qualitative research is the researcher him- or herself, often collecting the data through direct observation or interviews. So, the first instrument for this study is the researcher herself, and the second instrument is observation in the form of checklists. They are two kinds of checklist that were applied to answer the research questions. First, the checklist used to analyse the relevance of the materials with the cognitive aspects which are contained in the 2013 English Standard Competence. Second, the checklist used to analyse the relevance of the materials with the psychomotor aspects which are contained in the 2013 English Standard Competence. The technique used to collect the data in this study was by conducting an observation. The observation dealt with all of the materials in the textbook and the relevance of it based on 2013 Curriculum. The researcher observed the data by using observation checklist. The observation was done through several steps. First, the researcher determined the textbook which is going to be analysed. Second, the researcher read and observed the materials of the textbook carefully. Third, the researcher compared the materials in the textbook with the 2013 English Standard Competence using checklist in order to know the relevance between the materials on the textbook to the 2013 English Standard Competence. The last, the researcher collected the data then analysed them. The data of this study were collected from English textbook entitled “Bright” for seventh graders of Junior High School published by Erlangga. In analysing the data, some steps were taken, they are: The researcher analysed the relevance of the materials with the cognitive aspects which are contained in the 2013 English Standard Competence. The researcher analysed the relevance of the materials with the psychomotor aspects which are contained in the 2013 English Standard Competence. The researcher described and elaborated the findings of the analysis. The researcher determined the conclusion. RESULT AND DISCUSSION The Presentation of the textbook entitled “Bright” “Bright” is an English textbook designed for seventh graders of junior high school. This textbook also designed to support the process of teaching and learning and it is developed for the compatibility to the 2013 English Standard Competence. “Bright” is printed in 196 pages. These pages are added with the preface, table of contents, feature of the textbook, mini dictionary, appendix, bibliography, and spaces for students’ notes. In total, there are 204 pages printed on this textbook. There are eight units presented in this textbook. In the first semester, the students will learn unit 1 to unit 4; and the rest of it will be taught for the next semester. On each unit, the textbook provides fun corner and reflection table. In the fun corner, the authors give riddle question. For the reflection table, the students could use it after learning each unit as the reflection what they are good at, what they are ok at, and what they are bad at. Furthermore, for each unit in this book is divided into two parts: Listening and Speaking Activities and Reading and Writing activities. The first part focuses on listening and speaking skills. The latter part focuses in reading and writing. Expressions, grammar, explanations, and specific vocabularies that the students need for each activity and the students need to know are introduced and presented at the beginning of the activities, so that the students could understand the materials better. The Relevance of the materials in the textbook entitled “Bright” with the 2013 English Standard Competences Here are the tables to present the final result of the analysis to check the relevance of the materials in this textbook with the 2013 English Standard Competence. The researcher analysed the relevance of the materials based on the third and fourth basic competences. The Relevance of the Materials with the Cognitive Aspects Table 1. The Conformity of Textbook Materials to the Third Basic Competence The Relevance The Third Basic Competence Relevant Sub-basic competence 3.1.1, 3.1.3, 3.1.4, 3.2.1, 3.2.2, 3.3.1, 3.3.2, 3.3.3, 3.3.4, 3.3.5, 3.4.2, 3.5.2, 3.6.1, 3.6.2 Partly relevant Sub-basic competence 3.1.2, and 3.4.1 Not relevant Sub-basic competence 3.5.1, and 3.5.3 According to the table above, it can be seen that there are some materials which are relevant, partly relevant, and not relevant with the third sub-basic competence. The materials which relevant with the sub-basic competence are be able to fulfil the purposes of the topic, language features, and social functions that are intended to be achieve by the students. While the materials which not relevant the sub-basic competence are not be able to fulfil all of the purposes of the topic, language features, and social functions that are stated in the third sub-basic competence. There are two materials which partly relevant with the third sub-basic competence, they are: the 3.2.1 and 3.4.1 sub-basic competence. The 3.1.2 sub-basic competence is comprehending social functions, text structures, and language features in leave taking expressions and the responses according to the contexts. Leave taking expression is becoming one part of the greeting material and not being explained in-depth. Only few examples of leave taking expression occur in the table of greeting and the responses. There are not exercises for the leave taking expression, so that the social functions cannot be achieved. Thus, the materials are partly relevant with the 3.1.2 sub-basic competence. The textbook does have material of personal informtion that is stated in the 3.4.1 sub-basic competence. The goal of the competence is the students will be able to comprehend social functions, text structures, and language features from spoken text to mention personal information, while the material of personal information in the textbook is presented in the form of written texts and examples. Therefore, the materials are partly relevant with the 3.1.2 sub-basic competence. The Relevance of the Materials with the Psychomotor Aspects Table 1. The Conformity of Textbook Materials to the Fourth Basic Competence The Relevance The Fourth Basic Competence Relevant Sub-basic competence 4.1.1, 4.1.3, 4.1.4, 4.2.1, 4.3.1, 4.3.2, 4.3.3, 4.3.4, 4.3.5, 4.4.2, 4.5.2, 4.6.2, 4.7.2 Partly relevant Sub-basic competence 4.1.2, 4.4.1, 4.5.1, 4.7.1 Not relevant Sub-basic competence 4.2.2, 4.6.1, 4.6.3 According to the table above, it can be seen that there are some materials which are relevant, partly relevant, and not relevant with the fourth sub-basic competence. The materials which relevant with the sub-basic competence are be able to fulfil the indicators that are intended to be done by the students. While the materials which not relevant the fourth sub-basic competence are not be able to fulfil all of the indicators that are stated in the fourth sub-basic competence. There are four materials which partly relevant with the fourth sub-basic competence, they are: the 4.1.2, 4.4.1, 4.5.1, and 4.7.1 sub-basic competence. The textbook does have material of personal informtion that is stated in the 4.1.2 sub-basic competence. The goal of the competence is the students will be able to constructing spoken text in the form of leave taking with the appropriate social functions, text structures, and language features according to the contexts. However, the material of leave taking expression in this textbook is becoming one part with the greeting material. So the leave taking material is not being explained in-depth. Thus, there is no exercise that could help the students to achieve the goal of 4.1.2 sub-basic competence. Therefore, the materials in the textbook are partly relevant with the sub-basic competence. The goal of the sub-basic competence 4.4.1 is the students will be able to comprehend the meaning of spoken information. While the exercise and the example of personal information in the textbook is in the form written text. Therefore, the indicators cannot be fulfilled and the materials in the textbook are partly relevant with the sub-basic competence. The goal of the sub-basic competence 4.5.1 is the students will be able to construct spoken text for mentioning personal information with the appropriate social functions, text structures, and language features according to the contexts. The textbook does have material of personal information in unit 1. While the exercise of personal information in the textbook is intended to make students be able to construct personal information in the form written text. Therefore, the indicators cannot be fulfilled and the materials in the textbook are partly relevant with the sub-basic competence. The textbook contains of the sub-basic competence 4.7.1. The purpose of the materials is to construct written text in the form of labels with the appropriate language features according to the contexts.This textbook provide exercises about labels. However, there is no activity that aims students to construct their own labels. The materials cannot fulfil the indicators stated. Thus, this textbook does not provide activity to construct written labels. Therefore, the material in the textbook is not relevant with the sub-basic competence and the materials in the textbook are partly relevant with the sub-basic competence. CONCLUSIONS AND SUGGESTIONS Conclusions This study is intended to analyse the relevance of materials in English textbook for seventh graders entitled “Bright” published by Erlangga to the 2013 English Standard Competence. The researcher analysed the materials relevance to the cognitive and the psychomotor domains. From the analysis, it can be concluded that the English textbook “Bright” is quite relevant with the 2013 English Standard Competence. The materials in the textbook are quite relevant with the cognitive aspects which are contained in the 2013 English Standard Competence. According to the tables presented in the chapter four, the third basic competences which objectives emphasize on cognitive domain are quite relevant with the 2013 English Standard Competence. There are sixteen tables for the third basic competences. There are twelve tables which show the materials are relevant with the basic competences, these materials could fulfil objectives of the main topics, language features, and social functions stated. There are two tables which show the materials partly relevant with the basic competences, these materials could only fulfil one objective or two objectives stated. There are only two tables that show the materials are not relevant with the competences stated, these materials cannot fulfil all of the objectives. The forth basic competences which objectives emphasize on psychomotor domain are also quite relevant with the 2013 English Standard Competence. There are eighteen tables for the fourth basic competences. There are eleven tables which show the materials are relevant with the basic competences, these materials could fulfil all of the indicators. There are four tables which show the materials partly relevant with the basic competences, these materials occur in the textbook but cannot fulfil the indicators stated. There are only three tables that shows the materials are not relevant with the basic competences stated in the 2013 curriculum, these materials do not occur in the textbook. According to the elaboration above, the materials in this textbook are quite relevant with 2013 curriculum, especially with the cognitive and the psychomotor aspects. There are more materials which relevant with the 2013 English Standard Competence than the materials which not. Therefore, this textbook is appropriate with the 2013 curriculum and suitable to be used in order to help the teaching and learning process in the classroom. Suggestions After finishing this research, the researcher would like to give suggestion for the teacher, the textbook writer, and the next researcher. The first suggestion is for the teachers, the teachers should be careful and selective in choosing the textbook to be used in helping them in the teaching and learning activities. They should choose textbooks that contain materials appropriate with the curriculum. The selected textbook should support the curriculum to achieve the instructional objectives. For the textbook writers, they have to follow certain criteria in developing the materials. The materials should be in line with the English Standard Competence stated in the curriculum. Moreover, the materials should be able to fulfil all of the indicators, the objective of the main topics, the objective of the language features, and the objective of the social functions related to the competences. Thus, the textbook will be relevant with the curriculum and appropriate to be used by teachers and students. For the next researcher, they can conduct the study which is intended to analyse the relevance of the materials of the same textbook to the 2013 curriculum and focuses on the activities that intended to be taught in the second semester. Otherwise, the next researcher can study other textbook with the different grade of the study and analyse the relevance of the materials to the 2013 curriculum. REFERENCES Ali, Muhammad. 2009. Pengembangan Kurikulum di Sekolah. Bandung: Sinar Baru Algensindo. Amri, Sofan. 2013. Pengembangan dan Model Pembelajaran dalam Kurikulum 2013. Jakarta: Prestasi Pustaka Publisher. Anderson, Lorin W. & Krathwohl, David R. 2001. A Taxonomy for Learning, Teaching and Assessing: a Revision of Bloom’s Taxonomy. New York: Longman Publishing. Ary, Donald. et al. 2010. Introduction to Research in Education. Canada: Wadsworth, Cengage Learning. Bloom B. S. 1956. Taxonomy of Educational Objectives, Handbook I: The Cognitive Domain. New York: David McKay Co Inc. Byrd. 2001. Textbook: Evaluation for Selection and Analysis for Implementation. In M. Celce-Murcia (Eds.), Teaching English as a Second or Foreign Language (3rd ed., pp. 415-427). US: Heinle & Heinle. Dave, R. H. 1975. Developing and Writing Behavioral Objectives. (R. J. Armstrong, ed.). Tucson, Arizona: Educational Innovators Press. Kementrian Pendidikan dan Kebudayaan. 2013. Kurikulum 2013: Kompetensi Dasar Sekolah Menengah Pertama (SMP)/ Madrasah Tsanawiyah (MTs). Jakarta: Mendikbud. Krathwohl, D. R., Bloom, B. S., and Masia, B. B. 1973. Taxonomy of Educational Objectives, the Classification of Educational Goals. Handbook II: Affective Domain. London: Longman Group Ltd. Nunan, David. 2003. Practical English Language Teaching. Singapore: McGraw Hill. Oliver, Albert. I. 1977. Curriculum Improvement: A Guide to Problems, Priciples, and Process, Second Edition. New York: Harper and Row, Publishers. Tarigan, H. G and Tarigan, D. 1990. Telaah Buku Teks Bahasa Indonesia. Bandung: Angkasa. Tomlinson, Brian. 2003. Developing Materials for Language Teaching. London: Continuum.